Radiant exposure effects on physical properties of methacrylate - and silorane-composites - Catelan, Anderson; Kawano, Yoshio; Santos, Paulo Henrique dos [UNESP]; Ambrosano, Gláucia Maria Bovi; Bedran-russo, Ana Karina; Aguiar, Flávio Henrique Baggio (Faculdade de Odontologia de Piracicaba - UNICAMP, 2014)
AIM: To evaluate the effect of different radiant exposures on the degree of conversion (DC), Knoop hardness number (KHN), plasticization (P), water sorption (WS), and solubility (S) of different monomer resin-based composites. METHODS: Circular specimens (5 x 2 mm) were manufactured from methacrylate and silorane composite resins, and light-cured at 19.8, 27.8, 39.6, and 55.6 J/cm2, using second-generation LED at 1,390 mW/cm2. After 24 h, DC was obtained using a FT-Raman spectrometer equipped with a Nd:YAG laser, KHN was measured with 50-g load for 15 s, and P was evaluated on the top and bottom surfaces by the percentage of hardness reduction after 24 h immersed in absolute alcohol. WS and S were determined according to ISO 4049. Data were subjected to statistical analysis (α=0.05). RESULTS: Methacrylate material presented higher DC, KHN, P, and WS than silorane (p<0.05). There was no difference in the S values (p>0.05). The increased radiant exposures improved only the KHN (p<0.05). In general, top surfaces showed higher DC and KHN than bottom, for both materials (p<0.05). The increase of the radiant exposure did not improve most physical properties of the composites and were monomer-base dependent. CONCLUSIONS: Chemical composition of the composite resins resulted in different physical properties behavior and could affect the clinical longevity of dental restorations, but overall these properties were not influenced by the different radiant exposures evaluated in the study.
Keywords: composite resins; polymerization; physical properties